Job Satisfaction as a Mediator between Work Motivation, Teamwork, and Employee Performance: A Study at Puskesmas Mokoau, Kendari - Muhamad Masri; Emma Rianti; La Hatani; Juharsah (Khazanah Sosial, 2025)
This study investigates the relationship between work motivation, teamwork, and employee performance, with job satisfaction as a mediating variable, at the Regional Public Service Agency Technical Implementation Unit (BLUD UPTD) of Mokoau Public Health Center, Kendari City. The study involved 62 respondents, consisting of State Civil Apparatus (ASN) and Government Employees with Contract Agreements (P3K). Data were collected through an online questionnaire and analyzed using SmartPLS 4.0. The instrument used a 5-point Likert scale to measure agreement levels across four main variables. The results indicate that work motivation has a statistically significant positive effect on job satisfaction but does not have a statistically significant effect on employee performance. Similarly, teamwork has a significant positive impact on job satisfaction but shows no significant direct effect on employee performance. Furthermore, job satisfaction does not significantly influence employee performance and does not mediate the relationship between work motivation and employee performance. These findings offer important theoretical and managerial implications, particularly for improving employee outcomes through enhanced motivation and teamwork within public health institutions.